EVALUASI USABILITY SISTEM INFORMASI MANAJEMEN APOTEK BERBASIS PROGRESSIVE WEB APPLICATION MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Ichsandi; Kurniawan, Ade Agung (Information Technology Education Department, 2026)
This study aims to evaluate the usability level of a Progressive Web App (PWA)-based pharmacy management information system called Siapotek, implemented at Apotek Madani. The system encompasses modules for sales, purchasing, stock management, BPOM reporting, room temperature monitoring, cash management, and drug demand forecasting using the Moving Average method. Evaluation was conducted using the System Usability Scale (SUS) method, consisting of 10 statements on a Likert scale of 1–5. Respondents comprised three individuals representing all active system users: a pharmacist, a pharmaceutical technician who also serves as cashier, and the pharmacy owner. The calculation results showed an average SUS score of 79.17, categorized as Good with an Acceptable status based on the adjective rating and acceptability scale. This study is limited to evaluating usability from the end-user perspective and does not cover technical system performance evaluation. Practically, the findings provide a reference for developers to improve the interface and enhance user experience. Socially, a system with good usability contributes to improving the efficiency of pharmaceutical services for the community. The originality of this research lies in the evaluation of a PWA-based pharmacy information system using SUS in the context of a small-scale pharmacy in Indonesia, which remains underexplored in existing literature.